Current Status of Latency Reversing Agents Facing the Heterogeneity of HIV-1 Cellular and Tissue Reservoirs - Ait-Ammar, Amina; Kula, Anna; Darcis, Gilles; Verdikt, Roxane; De Wit, Stephane; Gautier, Virginie; Mallon, Patrick W. G.; Marcello, Alessandro; Rohr, Olivier; Van Lint, Carine (Frontiers in Microbiology, 2020)
One of the most explored therapeutic approach aiming at eradicating the HIV-1 reservoirs is the “shock and kill” strategy which is based on HIV-1 reactivation in latently-infected cells (“shock” phase), while maintaining ART in order to prevent spreading of the infection by the neosynthesized virus. This kind of strategy would allow the “kill” phase during which latently-infected cells would then die from viral cytopathic effects or from host cytolytic effector mechanisms following viral reactivation. Several latency reversing agents (LRAs) with distinct mechanistic classes have been characterized to reactivate HIV-1 viral gene expression. Some LRAs have been tested in terms of their potential to purge latent HIV-1 in vivo in clinical trials, showing that reversing HIV-1 latency is possible. However, LRAs alone have failed to reduce the size of the viral reservoirs. Together with the inability of the immune system to clear the LRA-activated reservoirs and the lack of specificity of these LRAs, the heterogeneity of the reservoirs largely contributes to the limited success of clinical trials using LRAs. Indeed, HIV-1 latency is established in numerous cell types that are characterized by distinct phenotypes and metabolic properties, and these are influenced by patient history. Hence, the silencing mechanisms of HIV-1 gene expression in these cellular and tissue reservoirs need to be better understood to rationally improve this cure strategy and hopefully reach clinical success.